Trees and Shrubs for Difficult Sites - Zook, Erin L. (My University, 2000)
This publication lists trees and shrubs that can service in different areas of Kansas and their qualities.
MF2205_2000_02
Keywords: MF2205; Forestry; Environment and Natural Resources; MF